Pengaruh Mutu Biji Kopi dan Lama Perendaman Sari Bonggol Nanas terhadap Sifat Fisikokimia dan Sensori Kopi Dekafeinasi: The Effect of Coffee Bean Quality and Pineapple Core Extract Soaking Time on The Physicochemical and Sensory Properties of Decaffeinated Coffee - Zada Agna Talitha; Isnaini Rahmadi; Hafizh Fadlin Zilqarnain (Universitas Bumigora, 2026)
Robusta coffee is the dominant coffee commodity produced in Lampung Province and is known for its bitter taste, which is related to its high caffeine content. This study aims to evaluate the effect of coffee bean quality and the duration of soaking in pineapple juice on the physicochemical properties and sensory attributes of decaffeinated robusta coffee. The study was conducted using a factorial randomized block design with a combination of grade 1 and 4b coffee bean quality and a soaking time of 24 hours and 36 hours. The results showed that coffee bean quality had a significant effect on total titratable acidity, protein content, b value, and sensory flavor characteristics. The duration of immersion had a significant effect on total titratable acidity, b value, and overall sensory attributes. The combination of grade 4b coffee with 36 hours of immersion produced the best color characteristics based on L* value, while the combination of grade 4b coffee with 24 hours of immersion showed the highest panelist acceptance based on total sensory evaluation. In conclusion, pineapple core waste can be used as a safer and more environmentally friendly alternative method for decaffeinating Robusta coffee. Therefore, by utilizing pineapple core waste as a source of bromelain enzyme, it is expected to increase the added value of local coffee with sensory characteristics that remain appealing to consumers.